2013
DOI: 10.1007/jhep06(2013)031
|View full text |Cite
|
Sign up to set email alerts
|

Probing the two light Higgs scenario in the NMSSM with a low-mass pseudoscalar

Abstract: In this article we propose a simultaneous collider search strategy for a pair of scalar bosons in the NMSSM through the decays of a very light pseudoscalar. The massive scalar has a mass around 126 GeV while the lighter one can have a mass in the vicinity of 98 GeV (thus explaining an apparent LEP excess) or be much lighter. The successive decay of this scalar pair into two light pseudoscalars, followed by leptonic pseudoscalar decays, produces clean multi-lepton final states with small or no missing energy. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 162 publications
1
27
0
Order By: Relevance
“…This is particularly important in the regions of the parameter space with m h 0 1 < JHEP02(2014)048 These points are similar to those studied in a previous analysis [26] in the context of scalar Higgs decays h → a 0 1 a 0 1 . It should be noted that in order to obtain such a light a 0 1 the input parameters have to be carefully tuned.…”
Section: Jhep02(2014)048supporting
confidence: 81%
See 3 more Smart Citations
“…This is particularly important in the regions of the parameter space with m h 0 1 < JHEP02(2014)048 These points are similar to those studied in a previous analysis [26] in the context of scalar Higgs decays h → a 0 1 a 0 1 . It should be noted that in order to obtain such a light a 0 1 the input parameters have to be carefully tuned.…”
Section: Jhep02(2014)048supporting
confidence: 81%
“…This is favoured by the LHC observation of a Higgs boson with a mass in the 2 σ range 124 − 126.8 GeV (124.5 − 126.9 GeV) by ATLAS (CMS) [19][20][21][22]. It has also been shown that in some regions of the parameter space another light, singlet-like, Higgs (h 0 1 ) can also be present, with a mass around 98 GeV [23][24][25][26][27], motivated by the small excess in the LEP search for e + e − → Zh, h → bb [28][29][30], or even lighter [26,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies also suggested to exploit pair production processes at the LHC in order to distinguish the SM from the NMSSM and/or to look for a light singlet in this fashion [78][79][80][81][82][83]. Scenarios with a very light CP-odd (or CP-even) Higgs boson were addressed with several search proposals in direct production, unconventional light charged-Higgs decays, or cascade decays from SM-like / light singlet states; large Higgs-to-Higgs decays were also considered from the point of view of the SM-compatible nature of the observed state [84][85][86][87]. Recent studies of the properties of a light pseudoscalar in the NMSSM [88,89] have emphasized the relevance of indirect production modes for the investigation of this scenario at the LHC.…”
Section: Jhep04(2016)095mentioning
confidence: 99%